2010
DOI: 10.1118/1.3528125
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiograph‐based texture analysis and bone mineral density with three‐dimensional microarchitecture of trabecular bone

Abstract: Digital radiographs, widely available and economically viable, are an alternative method for evaluating bone microarchitectural structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 75 publications
2
17
0
1
Order By: Relevance
“…cross-sectional moment of inertia, hip axis length, cortical thickness, trabecular bone score, Hurst parameters). X-ray-based technology is becoming available to estimate these components of bone strength which may have a future role in fracture risk assessment [2023]. …”
Section: Bone Mineral Measurementsmentioning
confidence: 99%
“…cross-sectional moment of inertia, hip axis length, cortical thickness, trabecular bone score, Hurst parameters). X-ray-based technology is becoming available to estimate these components of bone strength which may have a future role in fracture risk assessment [2023]. …”
Section: Bone Mineral Measurementsmentioning
confidence: 99%
“…By now, they are very common among medical image analyzing tasks, especially for classification problems. 19,20 If the original gray-level image I of size U × V has Q different intensities, the co-occurrence matrix of I is of size Q × Q. It is defined by its components C α, d (i, j) according to Eq.…”
Section: Iic3 Haralick Co-occurrence Featuresmentioning
confidence: 99%
“…However, these techniques are not comparable to the method presented in the present study as they are based on projections of a 3-dimensional trabecular network on a 2-dimensional plane, whereas our method is applied to 2-dimensional sections obtained through the 3-dimensional trabecular network. Nevertheless, Ranjanomennahary et al very recently showed some significant correlation did exist between radiograph based texture analysis and µCT based unbiased 3-dimensional measures of trabecular microarchitecture 47 . Apostol et al compared 3-dimensional measures of micro-architecture based on 3-dimensional synchrotron radiation CT with more than 350 texture parameters obtained from simulated radiographs that were created from the synchrotron radiation CT data sets 48 .…”
Section: Discussionmentioning
confidence: 99%